Phytochemical Profile of Rhizophora apiculata, Bruguiera gymnorhiza, and Bruguiera cylindrica for Wood Identification - Andianto; Wahyudi, Imam; Sari, Rita Kartika; Pari, Gustan; Prayogo, Yanico Hadi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Identification of wood species that are difficult to distinguish from their anatomical structure can be done through phytochemical (extractive substance) profiling. This research aimed to analyze the phytochemical profile as a sorter for three species of mangrove wood from Indramayu and Cilacap Regencies, Indonesia, using the liquid chromatography-mass spectrum. The phytochemical markers of taxonomic were the dominant compounds only found in one wood species. The results showed that the three types of wood are dominated by phytochemicals dissolved in ethanol. The results of LCMS analysis of the ethanol extract showed that the phytochemical markers were triterpenoid, flavonoid, and fatty acyls glycoside groups for Rhizophora apiculata, steroid and naphthalene groups for Bruguiera gymnorhiza, and alkaloid as well as fatty amide group for Bruguiera cylindrica. The dominant compounds that characterize these can be used in sorting between mangrove wood species. Keywords: characterizer, compound, mangrove, phytochemicals